Hardening efficiency and microstructural changes during laser surface hardening of 50CrMo4 steel - Maharjan, Niroj (2022)
Laser surface hardening is an attractive heat treatment solution used to selectively enhance the surface properties of components by phase transformation. A quantitative parameter to measure the efficacy of hardening processes is still lacking, which hinders its application in industries. In this paper, we propose a simple approach to assess the effectiveness of the process by calculating its thermal efficiency. The proposed method was applied to calculate the hardening efficiency during different laser processing conditions. This study revealed that only a small portion of supplied laser energy (approximately 1–15%) is utilized for hardening. For the same laser system, the highest efficiency is achieved when surface melting is just avoided. A comparative study showed that pulsed lasers are more efficient in energy utilization for hardening than continuous wave laser. Similarly, the efficiency of a high‐power laser is found to be higher than a low‐power laser and an increase in beam absorption produces higher hardening efficiency. The analysis of the hardened surface revealed predominantly martensite. The hardness value gradually decreased along the depth, which is attributed to the decrease in percentage of martensite.